Mitosis: methods and protocols - Sharp, David J., Ed (Methods in molecular biology; 1136, 2014)
Mitosis: Methods and Protocols provides state-of-the-art overviews on the most important approaches currently used in mitosis research spanning from the analysis of single molecules in isolation to their utilization within the complex environment of the cell. The volume is divided into four parts, each focused on methods pertaining to distinct aspects of mitosis research. Part I presents approaches for visualizing and analyzing the dynamic behaviors of the spindle apparatus, the microtubule based machine that drives chromosome segregation. Part II focuses more generally on methods for studying and manipulating the microtubule cytoskeleton in cells and complex cell free extracts. Part III provides state of the art biophysical and high resolution microscopy approaches for assessing complex interactions between microtubules and microtubule-associated proteins in isolation as well as microtubule structure in cells. Part IV provides methods for studying the effects of cell shape on cell division, and methods for quantifying aneuploidy (aberrant chromosome number) which frequently results from mitotic defects and has been linked to human maladies ranging from birth defects to cancer. Written in the highly successful Methods in Molecular Biology series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and key tips on troubleshooting and avoiding known pitfalls. Authoritative and practical, Mitosis: Methods and Protocols seeks to provide diverse methods and new techniques to address new or old questions related to the mechanisms of mitosis.--